An Exploratory Factor Analysis for Measuring the Four Cs of Lower-grade Primary Students - Meta Br Ginting; Rispah Purba; Winny Sunfriska br Limbong; Amelia Amanda; Dwi Ribka Sitanggang (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to develop a valid and reliable measurement factor for the Four Cs tailored to lower-grade primary school students. This study employed a quantitative non-experimental scale development and validation design utilizing Exploratory Factor Analysis (EFA). Participants comprised 274 second-grade primary school students from ten schools, divided into two phases: an initial trial (n = 76) for item selection and a main EFA trial (n = 198). Data were collected through structured performance observation checklists administered during STEM-based constructive play activities, with dichotomous scoring subsequently analyzed using JASP. EFA initially yielded six factors; however, the sixth factor, comprising a single item, was excluded from the final model as it did not meet the minimum item requirement for a viable factor. Factor loadings across the five retained factors ranged from 0.413 to 0.992. Cronbach's alpha coefficients indicated adequate to excellent internal consistency across factors: the first factor (α = 0.912), the second factor (α = 0.856), the third factor (α = 0.716), the fourth factor (α = 0.796), and the fifth factor (α = 0.544), with an overall reliability of α = 0.884. The findings indicate that the Four Cs can be measured by five factors: effective communication-critical thinking skills, creative expression skills, collaboration skills, communication skills in problem-solving, and creating skills. This study highlights different results from the P21 learning framework, finding that effective communication fosters problem-solving and critical thinking skills, while collaboration encourages creativity and the creation of original works.